PERLINDUNGAN LINGKUNGAN SOSIAL MELALUI KEBIJAKAN PUBLIK TENTANG KAWASAN TANPA ROKOK (KTR) - Okinu Rahim; Juliansyah Juliansyah; Robiyandi Robiyandi; Uni W Sagena; Masjaya Masjaya (LPPM Politeknik Pratama, 2024)
This study aims to analyze the implementation, stages, and obstacles in public policies issued by the Kutai Kartanegara Regency government to protect the social environment of the community, through Regent Regulation Number 22 of 2022 concerning Smoke-Free Areas (KTR). This policy aims to reduce exposure to cigarette smoke in public places, in order to improve public health. The method used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The focus of this study is on policy analysis, socialization, the establishment of special smoking areas, controlling tobacco advertising, as well as law enforcement and the role of the community. The results of the study indicate that there are challenges in the implementation of the KTR Perbup, including low public awareness, limited resources, and lack of coordination between related parties. This study suggests the need for expanded socialization, strengthening the role of the community, consistent law enforcement, and closer collaboration between government, industry, academics, the community, and the media. With pentahelix synergy, it is hoped that the KTR policy can be more effective in creating a healthier and smoke-free environment in Kutai Kartanegara.